Staying idle or investing in prevention: The short-term and long-term impact of cost stickiness on firm value - Guochao Yang; Yuzhen Kuang; Bingcheng Li (China Journal of Accounting Studies (CJAS), 2020)
Current theories about cost stickiness explain the phenomenon from the perspectives of adjustment cost, optimistic management expectations, and agency costs. However, the economic implications implied by different theories are different. We find that, in general, cost stickiness will reduce firm value in the short-term, but increase it in the long-term. That is, cost stickiness has an intertemporal heterogeneous impact on firm value. Furthermore, we found that the intertemporal heterogeneous effect of cost stickiness on firm value is mainly manifested in enterprises with higher adjustment cost, more optimistic manager's expectations, and lower agent costs. The above findings suggest that cost stickiness is a rational choice made after weighing its short-term costs and long-term benefits. The results of the threshold regression model show that rapid adjustment of costs (anti-stickiness) in the short-term will reduce the firm value, while maintaining a modest cost stickiness can increase the firm value in the long run.
Keywords: 650; Cost stickiness; firm value; short-term and long-term impact; cost and benefit trade-of